COMPOUNDS OF BISMUTH AND ITS PORPHYRINE COMPLEXES: APPLICATION, STRUCTURE AND PROPERTIES - A. S. Gorshkova; V. D. Rumyantseva; A. F. Mironov (Тонкие химические технологии, 2018)
Bismuth and its compounds have been known since ancient times and now are widely used in practice in various fields. Bismuth use in medicine can be traced back to the Middle Ages, and its wide application is due to its very low toxicity - for most bismuth compounds it is less than for sodium chloride. Bismuth and its compounds, in particular salts, are used in medical practice in the treatment of diseases such as spirochetosis, gastric and duodenal ulcer, leishmaniasis and coronaviral infection, as well as in cancer therapy. In addition to solid preparations liquid peroral pharmaceutical forms have been developed for the treatment of diarrhea, colitis, ulcers etc. Bismuth preparations are used in stomatology for the treatment of inflammatory diseases of paradontium. The review considers the syntheses and properties of bismuth complexes with natural and synthetic porphyrins, which are used in medicine and other fields of science and technology. Considerable attention is paid to the structure features of bismuth porphyrins complexes, their dimeric structures, and the influence of various extra ligands. The counterion nature and structure make a substantial contribution in solving the problem of complexes stability. The central bismuth atom in these complexes extends far above the plane of the macrocycle due to the large ionic radius. Thus, the counterions action on the conformation, physicochemical properties and stability of metal porphyrins complexes is shown. A separate section is devoted to unique and interesting properties of bismuth porphyrins complexes, such as fluorescence and color variation of crystals.